Strategies for Auditory Display of Social Media. Issue 1 (January 2019) - Winters, R. Michael; Joshi, Neel; Cutrell, Edward; Morris, Meredith Ringel
Social media is an overwhelmingly visual medium, and we ask the simple question: How can the data and images of social media posts be transformed into something as meaningful and vivid in the auditory sense? Such a design would be useful for eyes-free browsing and could enhance the existing visual media. Our strategy first uses artificial intelligence systems to transform low-level input data into high-level sociocultural features. These features are then conveyed using a multifactored temporal design that uses speech, sonification, auditory scenes, and music.